Determination algorithms of smoke interface height in channel fire simulation: Data comparative analysis and experimental verification. (November 2022) - Zhang, Xi; Dang, Xiaoyuan; Li, Jie; Chao, Xiaojie; Zhang, Yulun; Chen, Kai
Abstract: Smoke layer interface height is an important safety parameter in channel fire accidents. This paper proposed and compared three determination algorithms to estimated smoke layer interface height in channel fire simulation based on the characteristics of smoke layer interface during one-dimensional propagation stage. Reduced-scale experiments were also conducted to verify the predicted results. Results show that the dis-alignment of pressure gradient and density gradient, as well as velocity shear could generate vorticity. And vorticity motivates air entrainment of hot smoke. The vorticity at smoke layer interface is the largest in vertical direction. The smoke layer interface could be characterized by vertical component of temperature gradient, the vorticity perpendicular to longitudinal slice and horizontal component of velocity, among which the temperature gradient method was found to be suitable for determining the smoke layer interface height. And the prediction results by temperature gradient method agree with experimental data and empirical results well.